Fuzzy logic based merging gap acceptance model incorporating driving styles and drivers’ personalities - Chai, Chen (2020)
Cognitive ability and decision-making process in the driving task vary among drivers. Differences in driving styles and driver’s personality affect driving behavior, risk-taking and responses under hazardous scenarios. An innovative fuzzy logic based gap acceptance simulation model is proposed to extract and predict gap acceptance behavior with driving styles and drivers’ personalities. The proposed approach models driver’s decision-making process by a fuzzy set of the input factors. Cognitions, such as perceptions of front gap and current velocity, are modelled as fuzzy inputs while decisions, such as deceleration, are modelled as fuzzy outputs. For each driver, weighting factors are applied to differentiate driver’s sensitivity to operational factors, such as front gap and relative velocity during gap acceptance behavior.